2018
DOI: 10.1111/mmi.13932
|View full text |Cite
|
Sign up to set email alerts
|

Insights into transcriptional silencing and anti‐silencing in Shigella flexneri: a detailed molecular analysis of the icsP virulence locus

Abstract: Transcriptional silencing and anti-silencing mechanisms modulate bacterial physiology and virulence in many human pathogens. In Shigella species, many virulence plasmid genes are silenced by the histone-like nucleoid structuring protein H-NS and anti-silenced by the virulence gene regulator VirB. Despite the key role that these regulatory proteins play in Shigella virulence, their mechanisms of transcriptional control remain poorly understood. Here, we characterize the regulatory elements and their relative sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(88 citation statements)
references
References 54 publications
(131 reference statements)
4
84
0
Order By: Relevance
“…Next, we searched for sequences required for VirB-dependent regulation of the ospD1 promoter. In previous work, we found that the sequences required for VirB-DNA binding in vivo and VirB-dependent regulation require a VirB-binding site consisting of a near-perfect inverted repeat with the sequence 5=-ATTT(C)C(A/T)(C/ T)N(A/G)(A/T)G(G)AAAT-3= (25,27,45). Since VirB-binding sites have been identified at a variety of positions upstream of ϩ1 (22,25,46,47), we scanned the 2-kb region upstream of the ospD1 ATG for putative sites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we searched for sequences required for VirB-dependent regulation of the ospD1 promoter. In previous work, we found that the sequences required for VirB-DNA binding in vivo and VirB-dependent regulation require a VirB-binding site consisting of a near-perfect inverted repeat with the sequence 5=-ATTT(C)C(A/T)(C/ T)N(A/G)(A/T)G(G)AAAT-3= (25,27,45). Since VirB-binding sites have been identified at a variety of positions upstream of ϩ1 (22,25,46,47), we scanned the 2-kb region upstream of the ospD1 ATG for putative sites.…”
Section: Resultsmentioning
confidence: 99%
“…However, subsequent macroarray analysis showed that ospD1 mRNA levels increased at 37°C but only in the presence of virB (33). Since our previous work on icsP showed that VirB is capable of remotely regulating from a cis-acting VirBbinding site located over 1 kb upstream of the icsP promoter (25,27), we reasoned that the VirB regulatory elements that control ospD1 may not have been captured in the initially analyzed 500-bp ospD1 promoter region (40). To address this, we examined an extended region upstream of ospD1 to identify key regulatory elements leading to the transcriptional control of ospD1.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The IcsP (SopA) protein is a protease that deactivates IcsA, the cell-pole-located actin-tail-polymerizing protein ( Fukuda et al, 1995 ; d’Hauteville et al, 1996 ; Shere et al, 1997 ; Wing et al, 2004 ). The icsP promoter is silenced by H-NS and VirB acts there as an anti-repressor; contact between the counteracting proteins may involve DNA dependent protein polymerization in vivo ( Weatherspoon-Griffin et al, 2018 ). The ospZ promoter is also controlled by a VirB/H-NS-dependent silencing/anti-silencing mechanism ( Basta et al, 2013 ).…”
Section: The Unusual Virb Regulatory Protein In S Flexnerimentioning
confidence: 99%
“…Partitioning occurs either by separating plasmid DNA bound by partitioning proteins along a localised concentration gradient (type I, ParAB systems), or by the assembly of dynamic, actin‐like filaments that push each plasmid away from the mid‐cell (type II, ParMR systems) (mechanisms reviewed by Ebersbach and Gerdes, ). Interestingly, VirB, which regulates genes both on the Shigella flexneri PAI (Watanabe et al , ) and elsewhere on the virulence plasmid (Wing et al , ; Le Gall et al , ; Weatherspoon‐Griffin et al , ), has significant homology to proteins involved in partitioning (i.e . ParB and SopB encoded by plasmids P1 and F respectively) (Watanabe et al , ).…”
Section: Introductionmentioning
confidence: 99%